PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MESIN PKS (PENGELOLAAN KELAPA SAWIT) PADA PT. SERUMPUN INDAH LESTARI MEDAN - Edi Sofian; Jul karnaen (Universitas Islam Sumatera Utara, 2019)
Marketing strategies relating to the activity of increasing volume of product sales are implementing marketing strategies. Product quality, price, and promotion are important things that can influence purchasing decisions. The better the quality of the product in satisfying customers, then can cause high purchasing decisions anyway. The product has a direct pemgaruh to purchase decisions. With the increasing ability of a product it will be superior in competing so that customers will be satisfied. Customer satisfaction is also influenced by price and promotion. The purpose and objectives of this research is to measure and acknowledge and analyze the quality of products, prices and promotions on the decision of purchasing the MCC machine (palm oil management) at PT. Serumpun Indah Lestari Medan.The data analysis technique is a simple linear regression. The samples studied were as much as 73 people. The results of the research are beerinfluence on purchasing decisions. Price affects the purchase decision. Promotion to purchase decisions. And variable-free products, prices and promotions simultaneously (together) affect the variable Y (purchase decision). A 85.6% variation in product value, price and promotion is determined by the role of variation by sentence such as product, price and promotion in influencing the decision to purchase research advice the price effect is further improved due to its influence Very minimum. So the manager is required to further increase the purchase decision related prices.